Management of Strengthening Democracy Education in the Profile of Pancasila Students (An Analysis of Student Involvement in Five Major Demonstrations in Indonesia Over the Last Decade) - Masut, Vinsensius Rixnaldi; Sunarni, Sunarni (Universitas Negeri Malang, 2024)
This study examines the relationship between democracy education management in schools or universities and student political participation in demonstrations. Focusing on five major demonstrations in Indonesia over the past decade, it explores how democracy education shapes students' political awareness and involvement in social actions, while also contributing to the development of Pancasila Student profiles. The research uses a literature review method to delve into issues surrounding democracy education and the Pancasila Student profile. Empirical data was gathered from media reports, particularly Kompas daily, which has extensively documented student demonstrations in Indonesia. The findings suggest that democracy education management in educational institutions significantly influences student political participation in national and societal life, as envisioned in the Pancasila Student profile.